Kaji Numerik Pengaruh Beban Dinamik Terhadap Ketebalan Lapisan Film Dan Tekanan Hidrodinamik Pada Journal Bearing Menggunakan Finite Difference Method - Fadila Alfandi; Dedi Rosa Putra Cupu; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
One of the components used to hold the shaft that transmits power and rotation is the journal bearing. Journal bearing has the advantage of being able to withstand large loads and high rotation, however, journal bearing has a weakness, which is high friction. This high friction is minimized by means of lubrication, where the lubricant forms a film layer which functions as a separator between the journal and the housing so that mechanical contact does not occur. Journal bearing is usually work with dynamic loads on their operation, these dynamic loads affect the thickness of the film layer and the hydrodynamic pressure on the journal bearing. The al approach with the finite difference method is one method to determine the thickness of the film layer and the hydrodynamic pressure on journal bearing due to dynamic loads. The finite difference method is used to solve the differential equations in the dynamic load bearing Reynolds journal equation.The dynamic load acting on the journal bearing is the influence of non-dimensional amplitude and non-dimensional frequency. The nondimensional amplitude was varied from 0.1 to 0.5, while the non-dimensional frequency was varied π / 4, π / 2, π, 2π, 4π, and the observed time was 0.00 s to 0.09 s The conclusion is that the load on the journal bearing is directly proportional to the hydrodynamic pressure and inversely proportional to the thickness of the film layer with a maximum hydrodynamic pressure of 3,313 kPa and a minimum film layer of 32.92 μm, and the load of the journal bearing is directly proportional to the eccentricity ratio. The maximum eccentricity ratio is 0.675. Meanwhile, non-dimensional amplitude affects hydrodynamic pressure and non-dimensional frequency affects changes in hydrodynamic pressure with time. Keyword: Journal Bearing, Hydrodynamic, FDM, Dinamic Load